Novel Haemoproteus parasite lineage in Hooded Vultures (Necrosyrtes monachus) forms a distinct clade in Accipitriformes and highlights primer selection challenges in understudied avian hosts - Misa Shimizu; Oliver J. L. Fox; Jez Blackburn; Michael Colley; Colin Cross; Wendy James; John Jarju; Emmanuel Jatta; Naffie Sarr; Roger Walsh; Stephanie Key; Claudio Navarrete; et al. (Acta Parasitologica, 2026)

The Genomic Signature of Demographic Decline in a Long‐Distance Migrant in a Range‐Extreme Population - George Day; Thomas Bolderstone; Greg J. Conway; Tony Cross; Tony Davis; Matilda Dolan; Mervyn Greening; Colin Neale; Ian Nicholson; Kim Nicholson; Ann Ward; Nik Ward; et al. (Molecular Ecology, 2025)
Migratory birds are inherently vagile, a strategy that may reduce the impacts of habitat loss and fragmentation on genetic diversity. However, specialist resource requirements and range‐edge distribution can counteract these benefits. The European nightjar ( Caprimulgus europaeus ) is a long‐distance migratory bird and resource specialist. Like other long‐distance migrants, nightjar populations have declined across the British Isles and Northwestern Europe over the past century. With this decline well documented in the British Isles, there is a need to quantify its genetic impacts. We applied full genome resequencing to 60 historic (1841–1980) and 36 contemporary British nightjars. Nightjars exhibited a statistically significant 34.8% loss in heterozygosity and an increase in inbreeding over the last ~180 years, showing a departure from panmixia towards weak spatial structure in the modern population. Such fine‐scale structuring in migratory birds is rare. Our results provide a case study of fragmentation's impact on a species with specialist resource requirements at its range limit. Similar demographic declines in nightjars and other long‐distance migrants across Northern and Western Europe suggest that genetic patterns seen in the British population may reflect those in other nightjar populations and European avifauna. Whilst our results indicate no immediate conservation concern, they depict a trajectory of declining genetic diversity, increasing inbreeding and genetic structure, potentially shared with other migratory species. Our study highlights the value of applying spatiotemporal population genetics analysis to migratory birds, despite their inherent vagility.

An investigation of an outbreak of Salmonella Typhimurium infections linked to cantaloupe – United States, 2022 - Sharon Seelman Federman; Erin Jenkins; Cullen Wilson; Arturo DeLaGarza; Colin Schwensohn; Benjamin Schneider; Johnson Nsubuga; Robert Literman; Allison Wellman; Brooke M. Whitney; Rebecca L. Bell; Kerri Harris-Garner; et al. (Food Control, 2024)

From the environment into the biomass: microplastic uptake in a protected lamprey species - Flora Rendell-Bhatti; Colin Bull; Richard Cross; Ruairidh Cox; Gbotemi A. Adediran; Elma Lahive (Environmental Pollution, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Characterisation and expression of SPLUNC2, the human orthologue of rodent parotid secretory protein - Lynne Bingle; Frances A. Barnes; Hayley Lunn; Maslinda Musa; Steve Webster; C. W. Ian Douglas; Simon S. Cross; Alec S. High; Colin D. Bingle (Histochemistry and Cell Biology, 2009)